Analisis Kekaburan Norma Hukum dan Risiko Maladministrasi dalam Tata Kelola BPI Danantara (Jurnal Sosial Humaniora dan Pendidikan, 2025)
The establishment of the Danantara Investment Management Agency (BPI Danantara) as a state-owned enterprise superholding company through Law No. 1 of 2025 on State-Owned Enterprises and Government Regulation No. 10 of 2025 on the Organization and Governance of BPI Danantara has significant implications for the architecture of state asset management. Although aimed at improving efficiency and optimizing state assets, the institutional regulatory design of Danantara contains a number of legal ambiguities that could potentially lead to maladministration. This study aims to critically examine the inconsistencies and normative ambiguities in the legal instruments governing BPI Danantara and their implications for the principles of state administrative law, particularly the principles of legality and legal certainty. A legal-normative approach is employed through an analysis of regulations based on the principles of good governance. The main findings reveal that the BPI Danantara regulations, particularly Article 9G, which does not classify Danantara administrators as state administrators, as well as the use of optional norms such as the phrase “may” in the formation of the Monitoring and Accountability Committee in Article 24, have created legal uncertainty. This situation not only has the potential to cause of maladministration but also threatens accountability and transparency. Such institutional design creates a gray area that leads to abuse of authority. In this context, the case of 1Malaysia Development Berhad (1MDB) is a relevant example of how a loose institutional structure can lead to systemic corruption scandals, with significant impacts on fiscal credibility and the country's reputation. Ultimately, this can reduce public trust and the country's fiscal credibility in the eyes of global investors. Therefore, regulatory reform is a strategic urgency to clarify legal ambiguity and strengthen the effectiveness of external oversight institutions to ensure integrity, transparency, and accountability at BPI Danantara.